Effect of Vacuum Sealing on Quality Attributes of Tomato Paste Assessed by Gamma Radiations - Awais, Muhammad; Muhammad, Ali; Asif, Hafsa; Wisal, Shakoor; Khan, Salman; Khan, Fatima Afzal; Khan, Shahab; Ali, Ahmad (Indus Journal of Bioscience Research, 2025)
The aim of this research study was to utilize two preservative techniques: vacuum sealing and irradiation for food-processed stuff, both playing a vital role in preservation. Vacuum sealing prevents the sample from further contamination from the environment, and irradiation deactivates and denatures the microorganisms already present in tomato samples. In this study, we sealed and applied different doses of gamma radiation, i.e., 1KGy, 2KGy, and 3KGy. We observed the effect of irradiation on the following parameters: total soluble solids (TSS), power of hydrogen-ion concentration (pH), titratable acidity (TA), and ascorbic acid concentration. The processed tomatoes were treated with gamma irradiation, and the processed samples were evaluated. Irradiation causes minimal modifications in flavor, color, nutrients, taste, and other quality attributes of food. Tomatoes were irradiated at 1KGy, 2KGy, and 3KGy doses. It was observed that variations occurred during processing in all processed samples. There were no significant differences noted in the weight of all processed samples. The overall results indicate that no nutrient loss was observed in experimental samples. In some samples, values were slightly increased, while in others, they were slightly decreased when compared to control samples. Gamma irradiation could be the best technique for quality evaluation in the processing of other agricultural products. This study found ionizing radiation effective in extending the shelf life of vacuum-packed tomato paste. Gamma radiation at 2KGy and 3KGy preserved nutritional properties while enhancing shelf life. Irradiation can minimize food loss by disinfecting grains, legumes, fruits, and tubers, reducing crop infestations caused by insects and spoilage.